Neuropsychiatric Predictors of Post‐Injury Headache After Mild‐Moderate Traumatic Brain Injury in Veterans. Issue 4 (29th March 2016) - Bomyea, Jessica; Lang, Ariel J.; Delano‐Wood, Lisa; Jak, Amy; Hanson, Karen L.; Sorg, Scott; Clark, Alexandra L.; Schiehser, Dawn M.
Abstract : Objectives: To determine differences in neuropsychiatric complaints between Veterans with mild to moderate traumatic brain injury (TBI), with and without headache, compared with Veteran controls, and to identify neuropsychiatric predictors of headache severity. Background: Mild to moderate TBI is a common occurrence in Veterans, and is frequently associated with complaints of headache. Neuropsychiatric complaints are also common among individuals who have sustained head injury, although the relationship between these factors and headache after injury is unclear. Research is needed to comprehensively determine differences between individuals with mild to moderate traumatic brain injury who differ with respect to headache, and which injury, psychological, or sleep and fatigue factors predict headache severity. Methods: A cross‐sectional study compared 85 Veterans in three groups (positive for TBI and headache, positive for TBI without significant headache, and a control group) on a set of injury characteristics and neuropsychiatric variables. Correlates of headache severity were examined, and a regression model was used to identify significant independent predictors of headache severity. Results: Individuals with mild to moderate TBI and headache endorsed significantly greater neuropsychiatric symptoms than participants in the other groups (ηp 2 = .23−.36) Neuropsychiatric complaints, as well as presence of posttraumatic amnesia, were correlated with headache in the subsample with TBI ( r s = .44−.57). When entering all predictors into a regression model, only fatigue represented a significant independent predictor of headache severity (β = .59, R 2 = .35). Conclusions: Rather than being a global risk factor, mild to moderate TBI was associated with poorer mental health outcomes, particularly for those who endorse headache. Findings underscore the possibility that Veterans with history of TBI who present with complaints of headache may represent a particularly vulnerable subgroup. Additionally, our findings suggest that clinical outcomes may be improved in those with neurotrauma by incorporating a focus on fatigue in treatment.